Threatening criminals and marginalized individuals: Frames and news conventions in reporting of radicalization and violent extremism. (September 2019) - Larsen, Anna Grøndahl
The phenomenon of so-called foreign fighters has in recent years attracted renewed public interest regarding why young people who have grown up in Western, democratic countries come to accept and engage in politically motivated violence, and these issues have received extensive news attention. Based on analysis of news texts published in four major Norwegian news outlets throughout 2014 and 2015, and supplemented with in-depth interviews with reporters, the present article investigates how radicalization and violent extremism are framed in the news, including how news conventions contribute to shape the ways in which these issues are defined in public debate. The analysis shows that authority definitions prevailed. 'Radicalized' individuals were predominantly presented as threats and criminals to be dealt with in the judicial system. A 'marginalization approach' was, however, also present in the reporting. This was partly due to reporters' efforts to bring personalized human-interest stories, which, to some extent, served to broaden the overall range of depictions. Simultaneously, issues pertaining to radicalization were mainly discussed at micro- and mesolevels, and more abstract political or systemic explanations not actualized by specific events or easily concretized through foregrounding specific individuals were largely absent. The article contributes new insights into characteristics of public discourses of radicalization and violent extremism, and how these are constructed in the intersection between news conventions and (elite) sources.